Suppression of non-radiative recombination to improve performance of colloidal quantum-dot LEDs with a Cs2CO3 solution treatment - Nguyen, Huu Tuan; Ryu, Shinyoung; Duong, Anh Tuan; Lee, Soonil (Nanotechnology, 2021)
We report a five-fold luminance increase of green-light-emitting CdSe@ZnS quantum-dot LEDs (QLEDs) in response to treatment with a 2-ethoxyethanol solution of cesium carbonate (Cs2CO3). The maximum luminous yield of Cs2CO3-treated QLED is as high as 3.41 cd A-1 at 6.4 V. To elucidate device-performance improvement, we model measured currents as the sum of radiative and non-radiative recombination components, which are respectively represented by modified Shockley equations. Variations in model parameters show that a shift in Fermi level, reduction of barrier heights, and passivation of mid-gap defect states are the main results of Cs2CO3 treatment. In spite of a large luminance difference, light-extraction efficiency remains the same at 9% regardless of Cs2CO3 treatment because of the similarity in optical structures.
Keywords: Colloidal quantum dots; Device performance; Improve performance; Light-extraction efficiency; Non-radiative recombinations; Optical structures; Shockley equation; Solution treatments; Cs2CO3 treatment; Defect passivation; Fermi level shift; Modified Shockley equation; Non-radiative recombination; Quantum-dot LED